FOSTERING LEARNER AUTONOMY THROUGH PROJECT-BASED LEARNING - Diah Wulansari Hudaya, - (2018)
Passive students and the teachers' dominance in the EFL classrooms practices are common phenomena in the Indonesian contexts. However, the students need to be autonomous to be successful both in their classroom and their real life. As projectbased learning is believed to develop learner autonomy, this study aimed at investigating how project-based learning fostered learner autonomy in an EFL classroom referring to Holec's (1981) and Kumaradivelu's (2003) concept of learner autonomy. This study used qualitative descriptive research design at six senior high school students. The data were collected through observation, interview, and students' journals. The results of data analysis revealed that the activities in all stages of project-based learning have fostered learner autonomy in terms of determining learning objective, materials and sources, activities to do, using appropriate learning strategies for certain task, monitoring and evaluating the learning progress and results, and working cooperatively. There are also other findings. First, the students were in the highest degree of autonomy during the implementation stages. Second, the teacher played important role in fostering learner autonomy and the teacher's involvement in the right time could help them in developing their autonomy. Third, the students' autonomy could take in different degree depending on their learning progress. Fifth, the students needed to be prepared to be guided through a continuous process to be able to learn autonomously. Sixth, the concept of learner autonomy was related closely to the use of learning strategies. Lastly, there were advantages of project-based learning besides fostering learner autonomy as well as the constraints during the implementation. Based on the findings, it is recommended for the educational authorities to fully support the teachers and students in developing learner autonomy.